RE(VIEWING) THE CONSTITUTIONAL COURT’S DECISION IN SIDUMO - Jonathan Partington; Adriaan van der Walt (Obiter, 2022)
In Sidumo v Rustenburg Platinum Ltd (2007 12 BLLR 1097 (CC); 2007 28 ILJ 2405 (CC); 2008 2 SA 24 (CC)) the Constitutional Court made two findings of immense significance for dismissed employees: firstly, the court rejected the use of the socalled “reasonable employer” test in our law, which required arbitrators and courts evaluating the fairness of a dismissal for proven misconduct to treat the employer’s decision on sanction with a measure of deference; and secondly, on scrutiny of the more controversial issue before the court, to wit the basis, if any, upon which arbitrators are obliged to make reasonable decisions, the court (in confirming that arbitrators remain so obliged) held that the obligation to do so suffuses section 145 of the LRA ,and the extended review grounds of PAJA do not apply. In the present article these conclusions are critically analysed and evaluated, and a number of submissions are made, inter alia: it is submitted that the Constitutional Court’s rejection of the “reasonable employer” test was premised on a fundamental misinterpretation of what the test postulates; it is submitted that while the court’s attempt to locate the reasonableness standard within the LRA was perhaps justifiable, the court failed to consider properly, or indeed at all, the wording of section 145 and its history, with the consequence that the court failed to appreciate that section 145 (save on an unduly strained interpretation) could not conceivably be construed to cater, in itself and without more, for the scope of the constitutional right to just administrative action; and further, that the labour landscape post-Sidumo is one bathed in greater uncertainty. In conclusion, the authors pose the question whether, on a review of Sidumo, the Constitutional Court should not be considered to have fallen short of fulfilling its constitutional obligations under the rule of law.